Taylor swift ebook Superstar!. - Corey, Shana (Step into Reading., 2025)
Taylor Swift is a singer, songwriter, and superstar! Fans ages 4-6 will love learning about their favorite music icon in this Step 2 biography! Is your child a Swiftie in their "wanting to know more" Era? This biography is the perfect fit! Follow the story of Taylor's life—from her childhood growing up on a Christmas Tree farm in Pennsylvania all the way to her sold-out international Eras Tour! This biography uses simple text, short sentences, and full-color illustrations to help new readers learn all about the life, albums, tours, and phenomenal impact of global sensation Taylor Swift! Step 2 Readers use basic vocabulary and short sentences. They are perfect for children who recognize familiar words and can sound out new words with help.